Pengaruh Memorable Tourist Experience terhadap Storytelling Behavior melalui Perceived Value Pasca Pandemi Covid-19 - Eny Endah Pujiastuti; Didik Indarwanta; Ellena Wardani (Universitas Diponegoro, 2023)
Destination image can be used to strengthen brands and change markets. Brands can be formed with marketing communication strategies, one of which is using storytelling. The purpose of this study is to prove the effect of memorable tourist experience on storytelling behavior through perceived value in the post-pandemic period. The research was conducted at the Gajah Mungkur Reservoir tourist destination. The sample criteria used are tourists who have visited at least 2x (twice). The data was collected using the google form and 160 effective questionnaires were collected which would then be processed using the AMOS Structural Equating Modeling (SEM). Research shows: (1) Memorable tourism experience has a significant effect on perceived value; (2) Perceived value has a significant effect on storytelling behavior; (3) Memorable tourism experience has a significant effect on storytelling behavior; (4) Memorable tourism experience has a significant effect on storytelling behavior through perceived value. In suggestions for tourist destinations are that managers create a pleasant experience so that it is still stored in the memories of tourists and becomes a very memorable tourist experience. Citra destinasi dapat digunakan untuk memperkuat merek dan mengubah pasar. Merek dapat terbentuk dengan strategi komunikasi pemasaran, salah satunya dengan menggunakan storytelling. Tujuan penelitian ini adalah untuk membuktikan pengaruh memorable tourist experience terhadap storytelling behavior melalui perceived value pasca pandemi. Penelitian dilakukan di destinasi wisata Waduk Gajah Mungkur. Kriteria sampel yang dipergunakan adalah wisatawan yang baru berkunjung minimal 2x (dua kali). Pengumpulan datanya dengan menggunakan google form dan terkumpul 160 kuesioner efektif yang selanjutnya akan diolah menggunakan Structural Equating Modeling (SEM) AMOS. Penelitian menunjukkan: (1) Memorable tourism experience berpengaruh signifikan terhadap perceived value; (2) Perceived value berpengaruh signifikan terhadap storytelling behavior; (3) Memorable tourism experience berpengaruh signifikan terhadap storytelling behavior; (4) Memorable tourism experience berpengaruh signifikan terhadap storytelling behavior melalui perceived value. Saran bagi destinasi wisata adalah pengelola menciptakan pengalaman yang menyenangkan sehingga masih tersimpan di dalam memori wisatawan dan menjadi pengalaman yang sangat berkesan (memorable tourist experience).